Análise não-linear e simulações de oscilações de sub-vão em linhas de transmissão - Oliveira, Agamenon Rodrigues Eufrásio (1982)
The majority of the published research used a linearized version of the mathematical model describing the dynamics of sub-span oscillations. The problem was always reduced to a flütter-problem. A definition for the amplitude of the limit cycle and its stability were not possible using this linearized approach. This investigation attacks the problem using nonlinear analysis. The lift and drag coefficients of a cylinder in the wake of another are represented by mathematical models using experimental data which are available from wind-tunnel tests. The coefficients of the model are chosen to give the best representition of the data in the range of interest. The linear parts of the expressions for CL and CD were then used to conduct a preliminary investigation to determine the stability zones as well as the critical wind velocities. The used model was nonlinear and a nonlinear analysis was adopted using multiple-time scale and the asymptotic approximations of Kryloff and Bogoliuboff. The expressions for CL and CD were next represented by second arder polynomials. These were used to study the Limit cycles and, to determine their stability. A harmonic balance proved to be adequate for this investigation. Digital and analog simulation were tried to verify the mathematical predictions. The agreement in trends was confirmed.